Neo Hisbah Institution: Capturing the Halal Supervision Mechanism at Badan Penyelenggara Jaminan Produk Halal (BPJPH) Indonesia - Ririn Noviyanti (Iqtishodia: Jurnal Ekonomi Syariah, 2020)
All forms of economic activity must run fairly and in accordance with Islamic law. The purpose of this paper is to conduct an in-depth study of the suitability between the supervisory mechanism of the Hisbah institution in the past and the supervisory mechanism carried out by the Halal Product Guarantee Agency (BPJPH). This research is qualitative with data collection techniques using documentation. Data analysis using content analysis method. The conclusion of this study shows that the supervisory mechanism implemented by BPJPH is in accordance with the principles of hisbah in the past, both in terms of procedures and regulations. In contrast, the scope of supervision at BPJPH are narrower than the scope of supervision tasks in the past.